The Tradition of Eating Bajamba in Fostering Cohesiveness and a Sense of Belonging in Nagari Kamang Mudiak - Miladiah, Fakhriatul Ulfa; Desina, Mela; Litania, Nenny; Chairunnisa, Chairunnisa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Makan bajamba is a traditional Minangkabau communal dining practice that embodies deep social, symbolic, and psychological meanings. Beyond fulfilling biological needs, this tradition functions as a cultural mechanism for strengthening social cohesion, collective identity, and a sense of belonging within indigenous communities. This study aims to explore the practice of makan bajamba and its contribution to fostering social cohesion and sense of belonging among the people of Nagari Kamang Mudiak, Agam Regency, West Sumatra. Employing a qualitative approach with a case study design, data were collected through participant observation during a baralek gadang (traditional wedding ceremony) and in-depth interviews with bundo kanduang and juwaro who play key roles in the ritual. The findings reveal that makan bajamba is a highly structured customary ritual that reflects values of equality, togetherness, and respect for Minangkabau social structure. Seating arrangements, food presentation, and the shared practice of eating from a single tray serve as symbolic expressions that strengthen emotional bonds among community members. This collective experience enhances social cohesion and fulfills essential components of sense of belonging, particularly belongingness and valued involvement. Moreover, makan bajamba acts as a medium for intergenerational transmission of cultural values and identity amid the pressures of modernization. The study highlights the significance of local cultural practices in sustaining cultural identity while promoting psychosocial well-being within indigenous communities.